2012
DOI: 10.1007/s11606-012-2160-z
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Beliefs Are Associated with Medication Adherence in Older Asthmatics

Abstract: BACKGROUND: Empirical research and health policies on asthma have focused on children and young adults, even though asthma morbidity and mortality are higher among older asthmatics. OBJECTIVE: To explore the relationship of asthmarelated beliefs and self-reported controller medication adherence in older asthmatics. DESIGN: An observational study of asthma beliefs and self-management among older adults. PARTICIPANTS: Asthmatics ages ≥60 years (N=324, mean age 67.4±6.8, 28 % white, 32 % black, 30 % Hispanic) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 30 publications
2
62
1
11
Order By: Relevance
“…5,9-13 Demographic characteristics included age, race, education, income and English proficiency. 5,6 Other variables that might affect adherence strategies included patient birthplace and past experiences with asthma (e.g., intubation, years with asthma).…”
Section: Other Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…5,9-13 Demographic characteristics included age, race, education, income and English proficiency. 5,6 Other variables that might affect adherence strategies included patient birthplace and past experiences with asthma (e.g., intubation, years with asthma).…”
Section: Other Variablesmentioning
confidence: 99%
“…Studies framed according to the Common Sense Model of Self-Regulation 20 have found that medication adherence is associated with accurate conceptualizations (beliefs) of asthma and favorable opinions of ICS. 5,21 Three questions from the validated Brief Illness Perceptions Questionnaire and used extensively in prior research were used to measure asthma beliefs. 5,22,23 Subjects were asked whether they expected their doctors to cure their asthma and whether they thought they would always have asthma.…”
Section: Other Variablesmentioning
confidence: 99%
See 3 more Smart Citations